Stereotactic Cavity Irradiation or Whole-Brain Radiotherapy Following Brain Metastases Resection—Outcome, Prognostic Factors, and Recurrence Patterns - El Shafie, Rami A.; Dresel, Thorsten; Weber, Dorothea; Schmitt, Daniela; Lang, Kristin; König, Laila; Höne, Simon; Forster, Tobias; von Nettelbladt, Bastian; Eichkorn, Tanja; Adeberg, Sebastian; Debus, Jürgen; et al. (Frontiers in Oncology, 2020)
Introduction: Following the resection of brain metastases (BM), whole-brain radiotherapy (WBRT) is a long-established standard of care. Its position was recently challenged by the less toxic single-session radiosurgery (SRS) or fractionated stereotactic radiotherapy (FSRT) of the resection cavity, reducing dose exposure of the healthy brain. Patients and methods: We analyzed 101 patients treated with either SRS/FSRT (n=50) or WBRT (n=51) following BM resection over a 5-year period. Propensity score adjustment was done for age, total number of BM, timepoint of BM diagnosis, controlled primary and extracranial metastases. A Cox Proportional Hazards model with univariate and multivariate analysis was fitted for overall survival (OS), local control (LC) and distant brain control (DBC). Results: Median patient age was 61 (IQR: 56–67) years and the most common histology was non-small cell lung cancer, followed by breast cancer. 38% of the patients had additional unresected BM. 24 patients received SRS, 26 patients received FSRT and 51 patients received WBRT. Median OS in the SRS/FSRT subgroup was not reached (IQR NA–16.7 months) versus 12.6 months (IQR 21.3–4.4) in the WBRT subgroup (HR 3.3, 95%-CI:[1.5;7.2] p<0.002). 12-months LC-probability was 94.9% (95%-CI:[88.3;100.0]) in the SRS subgroup versus 81.7% (95%-CI:[66.6;100.0]) in the WBRT subgroup (HR 0.2, 95%-CI:[0.01;0.9] p=0.037). 12-months DBC-probabilities were 65.0% (95%-CI:[50.8;83.0]) and 58.8% (95%-CI:[42.9;80.7]), respectively (HR 1.4, 95%-CI:[0.7;2.7] p=0.401). In propensity score-adjusted multivariate analysis, incomplete resection negatively impacted OS (HR 3.9, 95%-CI:[2.0;7.4], p<0.001) and LC (HR 5.4, 95%-CI:[1.3;21.9], p=0.018). Excellent clinical performance (HR 0.4, 95%-CI:[0.2;0.9], p=0.030) and better graded prognostic assessment (GPA) score (HR 0.4, 95%-CI:[0.2;1.0], p=0.040) were prognostic of superior OS. A higher number of BM was associated with a greater risk of developing new distant BM (HR 5.6, 95%-CI:[1.0;30.4], p=0.048). In subgroup analysis, larger cavity volume (HR 1.1, 95%-CI:[1.0;1.3], p=0.033) and incomplete resection (HR 12.0, 95%-CI:[1.2;118.3], p=0.033) were associated with inferior LC following SRS/FSRT. Conclusion: This is the first propensity score-adjusted direct comparison of SRS/FSRT and WBRT following the resection of BM. Patients receiving SRS/FSRT showed longer OS and LC compared to WBRT. Future analyses will address the optimal choice of safety margin, dose and fractionation for postoperative stereotactic RT of the resection cavity.